MATERIAL FLOW STUDY DTTRING FRICTION STIR WELDING OF DISSIMILAR MATERIAL - KON KIT LUNG, KON KIT LUNG (Universiti Teknologi Petronas, 2012)
This research focuses on the material flow study of aluminium alloy 6092lSiC/25p metal matrix composite welded plate. In this research, friction stir welding is used as the joining method to join aluminium alloy 6061 and aluminium alloy 6092lSiC/25p metal matrix composite welded plate. Two different configurations are focused in this research. A4606l plate is placed at advancing side and AA6092 MMC is placed at retreating side in configuration I and vice versa in configuration 2. First of all, suitable FSW tool with tapered angle is designed and fabricated following by determine the acceptable FSW pararneters (feed rate and rotational speed) with least defects. FSW final nrn on both configurations are executed with acceptable parameters. Samples are collected from each configuration to be observed under optical microscope to achieve the main objective which is to study the material flow of silicon carbide in the weld zone in both configurations. The research has been successfully carried out and its findings showed that configuration 2 where AA6092 MMC is placed at advancing side has better FSW result wittt less wear at surface and minimal weld hole spotted. Apart from that, there is more SiC particles circulation from advancing to retreating side in configuration 2. This finding is proven by microhardness testing which showed that configuration 2 has average higher HV value as compared to configuration I and the zone with more sic particles gave higher HV value.